2012
DOI: 10.1017/s0317167100014001
|View full text |Cite
|
Sign up to set email alerts
|

CD226 Gly307Ser Association With Neuromyelitis Optica in Southern Han Chinese

Abstract: Background:Neuromyelitis optica (NMO) and multiple sclerosis (MS) are autoimmune diseases of the central nervous system with complex pathogeneses. NMO was once considered to be a severe variant of MS. There has been more evidence that a non-synonymous exchange (rs763361/Gly307Ser) in the gene for CD226 is linked to several autoimmune diseases including multiple sclerosis (MS). However, no studies have investigated the role of rs763361 in the pathogenesis of NMO.Objectives:The goal of our study is to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Other non-HLA genes exert an increase in relative risk for NMO/NMOSD pathogeneses that range from modest to high. This is the case for CYP7A1 that is associated with alterations in transcriptional regulation [ 59 ], IL17 which produces high levels of IL-17 [ 60 ], CD2 26 that affects T-cell signaling [ 61 ], PD1 that interferes in T-cell activation [ 54 ], CD4 0 that produces alterations in the TNFR family [ 62 ], and CD5 8 that is involved in cell adhesion [ 63 ]. Table 1 summarizes the presence of genetic variants associated with other NADs.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Other non-HLA genes exert an increase in relative risk for NMO/NMOSD pathogeneses that range from modest to high. This is the case for CYP7A1 that is associated with alterations in transcriptional regulation [ 59 ], IL17 which produces high levels of IL-17 [ 60 ], CD2 26 that affects T-cell signaling [ 61 ], PD1 that interferes in T-cell activation [ 54 ], CD4 0 that produces alterations in the TNFR family [ 62 ], and CD5 8 that is involved in cell adhesion [ 63 ]. Table 1 summarizes the presence of genetic variants associated with other NADs.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Interestingly, rs9272219 and rs1964995 have been associated with other autoimmune diseases such as rheumatoid arthritis and dermatomyositis in different populations (Eleftherohorinou et al, 2011;Hao et al, 2014). Few non-HLA candidate gene studies have been conducted in NMOSD (Asgari et al, 2012;Liu et al, 2012;Wang et al, 2012;Kim et al, 2014;Zhuang et al, 2015), and as far as we know, TMPO has not been previously identified as a susceptibility gene in GWAS, nor has it has been studied as a candidate gene for any autoimmune disorder. Although experimental evidence on the role of TMPO and LAP2 in autoimmunity is limited, it has been demonstrated that LAP2 binds to lamin B1 in vitro (Foisner and Gerace, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Other HLA class II risk alleles have been associated with NMOSD in different ethnic groups. A limited number of candidate gene association studies have also reported associations of NMOSD with individual polymorphisms in a few genes involved in immune function, including PD-1, IL-17, IL-7R, CD226, and CD58 (Asgari et al, 2012;Liu et al, 2012;Wang et al, 2012;Kim et al, 2014;Zhuang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analyses including a replication study showed that a common promoter SNP in CYP7A1 on chromosome 8q11‐q12 has a protective effect against the risk of NMO. Some studies aimed at determining whether MS‐associated SNPs and genes also contribute to NMO susceptibility have suggested the genetic contribution of CD226 , TNFRSF1A , and GPC5 for NMO. To date, there have been only a few reports that also included replication studies.…”
Section: Neuromyelitis Opticamentioning
confidence: 99%